2014
DOI: 10.1111/jvim.12368
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Early Magnetic Resonance Imaging in Dogs after Traumatic Brain Injury: 50 Cases

Abstract: BackgroundThe prognostic value of early magnetic resonance imaging (MRI) in dogs after traumatic brain injury (TBI) remains unclear.ObjectivesDetermine whether MRI findings are associated with prognosis after TBI in dogs.AnimalsFifty client‐owned dogs.MethodsRetrospective study of dogs with TBI that underwent 1.5T MRI within 14 days after head trauma. MRI evaluators were blinded to the clinical presentation, and all images were scored based on an MRI grading system (Grade I [normal brain parenchyma] to Grade V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 35 publications
6
63
4
1
Order By: Relevance
“…Similarly, in the study by Beltran and others (2014), unilateral and bilateral brainstem lesions were respectively classified with the higher MRI grade and had significant negative correlation with MGCS at presentation and patient follow-up scores, which is consistent with previous studies in people. This study also agreed with previous work in people in which poor outcome was significantly associated with brain herniation, skull fractures and larger intraparenchymal lesions.…”
Section: Role Of Imagingsupporting
confidence: 91%
See 3 more Smart Citations
“…Similarly, in the study by Beltran and others (2014), unilateral and bilateral brainstem lesions were respectively classified with the higher MRI grade and had significant negative correlation with MGCS at presentation and patient follow-up scores, which is consistent with previous studies in people. This study also agreed with previous work in people in which poor outcome was significantly associated with brain herniation, skull fractures and larger intraparenchymal lesions.…”
Section: Role Of Imagingsupporting
confidence: 91%
“…Recent studies in people have demonstrated that MRI findings can be valuable predictors of clinical outcome due to their high sensitivity for the detection of lesions such as non-haemorrhagic contusions, brainstem involvement and diffuse axonal injuries (DeQuesada and Chokshi 2014). In a recent veterinary study, MRI characteristics of TBI, such as volume of parenchymal damage and midline shift of the cerebral hemispheres, appeared to have clinical relevance due to their significant correlation with outcome (Beltran and others 2014). This study used a grading system modified from human medicine, where the severity and location of the lesions were taken into account (Table 1).…”
Section: Role Of Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…[23][24][25] The major drawbacks of MRI include accessibility, cost, and time necessary to complete the scan; however, recent work suggests that it can be a valuable prognostic tool, at least in dogs with head trauma. 26 Advances in task-based functional MRI (fMRI), resting-state fMRI (rs-fMRI), and arterial spin labeling (ASL) perfusion MRI have occurred at a rapid pace in recent years in humans. 27 These techniques for measuring brain function have great potential to improve the accuracy of prognostication for patients with traumatic coma.…”
Section: Neuroimagingmentioning
confidence: 99%